Some methods of signals compression and analysis of their effectiveness - Prokopenko, К. І. (Proceedings of National Aviation University (archive), 2003)
A series of widely used methods of speech signals compression is considered. The new methods such as the logarithmic delta-modulation, the algorithms of compression with the application of fast Fourier transformation at a binary partition of a signal fragment, the signal compression in the basis of eigenfunctions of a correlation operator are offered. The comparative analysis of algorithms effectiveness by the relative standard error criterion is carried out